Glyphosate concentration and phytotoxicity in Lactuca sativa Buttercrunch - Primo, Thais Agda Rodrigues da Cruz; Göde, Júlia Nercolini; Oliveira, Mariana Gomes; Ribeiro, Taciana Furtado; Sartor, Lucas de Bona; Magro, Renata Bulling; Skoronski, Everton (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
Agrochemicals, also known as agrotoxics or pesticides, have been widely used to control the proliferation of pests and weeds in agricultural crops to ensure high planting productivity. Among the most used pesticides in the world is the herbicide glyphosate (N-(phosphonomethyl) glycine), because it proves effective for controlling the annual and perennial growth of weeds in agriculture, forestry, urban areas, and domestic gardens. However, the spraying of this compound on a large scale has caused concern, since it accumulates in the topsoil and can generate negative environmental impacts and damage to human health, as it has toxic potential. Given the above, this study evaluated the phytotoxicity of agrochemical solutions glyphosate in different concentrations for the lettuce species Lactuca sativa Buttercrunch, considering number of germinated seeds, stem length, and root length as parameters of analysis. The concentrations of glyphosate tested were 0.001 mg. L-1; 0.1 mg. L-1; 0.5 mg. L-1; 1 mg. L-1 and 20 mg. L-1. The trial followed the procedures described by the United States Environmental Protection Agency. For the statistical analysis, were considered the number of germinated seeds of each treatment and the length of the roots and stem of each of the germinated seeds, which were inserted into equations for the definition of the percentage parameters of Germination Effect (%GE), Root Growth Inhibition (%RGI) and Germination Index (%GI). Analysis of variance (ANOVA) was performed to test for statistically significant differences among the groups and compared by applying the Tukey Test at the level of 5% significance. The results revealed that there was 62.62% RGI and a GI of only 0.37% in treatment with glyphosate solution with concentration of 20 mg. L-1, indicating that high concentrations of the herbicide have toxic effects for the growth of lettuce species Lactuca sativa Buttercrunch. Only the concentration of 20 mg. L-1 obtained a significant difference in relation to the other concentrations evaluated, including the control treatment for the variable "root growth". Thus, for future work it is recommended that glyphosate solutions with concentrations between 1 and 20 mg. L-1 be evaluated and tested for phytotoxicity, cytotoxicity and genotoxicity.